Use of Thorium in Thermal-Neutron Reactors: Different Types of Fuel Compositions in VVER-1000 Reactor Cell; Journal of Industrial Pollution Control; Vol. 32, iss. 2 - Naymushin A. G. Artem Georgievich; Chertkov Yu. B. Yuri Borisovich; Lebedev I. I. Ivan Igorevich; Anikin M. N. Mikhail Nikolaevich; Savanyuk S. N. Savva Nikolaevich (2016, 2016)
Title screen